THE EXIGENCY OF HUMAN RIGHTS APPROACHES IN THE INTERCEPTION OF COMMUNICATION BILL: AN EFFORT TO STRENGTHEN THE INDONESIAN CRIMINAL JUSTICE SYSTEMS - Suntoro, Agus; Utomo, Nurrahman Aji; Hermawan, Sapto (Jurnal Hukum dan Peradilan, 2020)
Tapping in a human rights perspective is a form of limitation of the right to privacy. As an effort to guarantee human rights protection, tapping as a part of The Interception of Communication Bill arrangements must be following the principles of human rights restrictions. Some of the anomalies in The Interception of Communication Bill appear in vague forms and open up the broad ways of potential violations of individual rights. For this reason, the principles of legality and prudence as a form of control over government actions need to offset the urgency of tapping. Data collection methods use discussions and interviews to enrich and test secondary data findings. This research stipulates that The Interception of Communication Bill use tapping as an induced instrument in criminal law enforcement. At the same time, tapping is regulated regardless of the readiness of the legal apparatus; this naturally raises technical problems in the matter of implementation and opens the door to abuse of authority. Furthermore, based on the need for comprehensive regulation, it is necessary to look at a comprehensive regulatory scheme in the legal system. The functional control that is in line with the tapping mechanism needs to look at the character of the Indonesian criminal justice system.